Characterization of renal cell carcinoma‐associated constitutional chromosome abnormalities by genome sequencing. Issue 6 (5th February 2020) - Smith, Philip S.; Whitworth, James; West, Hannah; Cook, Jacqueline; Gardiner, Carol; Lim, Derek H. K.; Morrison, Patrick J.; Hislop, R. Gordon; Murray, Emily; ,; Tischkowitz, Marc; Warren, Anne Y.; et al.
Abstract: Constitutional translocations, typically involving chromosome 3, have been recognized as a rare cause of inherited predisposition to renal cell carcinoma (RCC) for four decades. However, knowledge of the molecular basis of this association is limited. We have characterized the breakpoints by genome sequencing (GS) of constitutional chromosome abnormalities in five individuals who presented with RCC. In one individual with constitutional t(10;17)(q11.21;p11.2), the translocation breakpoint disrupted two genes: the known renal tumor suppressor gene (TSG) FLCN (and clinical features of Birt‐Hogg‐Dubé syndrome were detected) and RASGEF1A . In four cases, the rearrangement breakpoints did not disrupt known inherited RCC genes. In the second case without chromosome 3 involvement, the translocation breakpoint in an individual with a constitutional t(2;17)(q21.1;q11.2) mapped 12 Kb upstream of NLK. Interestingly, NLK has been reported to interact indirectly with FBXW7 and a previously reported RCC‐associated translocation breakpoint disrupted FBXW7 . In two cases of constitutional chromosome 3 translocations, no candidate TSGs were identified in the vicinity of the breakpoints. However, in an individual with a constitutional chromosome 3 inversion, the 3p breakpoint disrupted the FHIT TSG (which has been reported previously to be disrupted in two apparently unrelated families with an RCC‐associated t(3;8)(p14.2;q24.1). These findings (a) expand the range of constitutional chromosome rearrangements that may be associated with predisposition to RCC, (b) confirm that chromosome rearrangements not involving chromosome 3 can predispose to RCC, (c) suggest that a variety of molecular mechanisms are involved the pathogenesis of translocation‐associated RCC, and (d) demonstrate the utility of GS for investigating such cases.